Integrated procedure for vibration characterization of a magnetic bearing supported rotor delevitation system. (May 2016) - Bean, J.; van Schoor, G.; du Rand, C.P.
Highlights: The vibration characterization of a magnetic bearing supported rotor is presented. Numerical model and experimental rotor modal analyses validate bending modes. Analytical model and experimental modal analyses validate rigid body modes. Practical case study confirms validity of the proposed characterization procedure. Abstract: This paper considers an integrated procedure to verify and validate (V&V) the rotordynamic analyses of a magnetic bearing supported rotor delevitation system (RDS). Rotor-AMB (active magnetic bearing) systems in general have complex geometries which make accurate modelling thereof a difficult task. For this purpose, simple rotordynamic analyses methods, practical measurements, and finite element method (FEM) models are applied in an integrated framework to characterize the natural vibration frequencies of the system. First, a numerical model (Rayleigh's energy method) and an experimental modal analysis of the rotor-only are utilized to V&V the bending natural frequency estimates of a rotor FEM simulation model. Thereafter, an analytical model (two degree of freedom method) and a modal analysis of the integrated rotor-AMB system are employed to V&V the rigid body natural frequency estimates of a rotor-AMB FEM simulation model. Adjustments of the FEM models are realized using feedback to fine-tune the geometric, material, and operating properties of the discs, the rotor, and the AMBs. A practical case study of a RDS successfully demonstrates application of the integrated procedure, which ultimately facilitates improved correlation between FEM simulation and experimental results.